The Verses and Hadiths Contained in the interpretation of Suratu Ibrahim from the Sahih of Imam al-Bukhari: An Interpretative and Narrative Study - Hariyanto, Dididk; Billah, Md Masm; al-Gamidi, Muhammad Ali (Eximia, 2022)
This study mainly aims at highlighting the methods of Imam Al-Bukhari, that he applied in the interpretation of Surat Ibrahim in interpretation chapter from his Sahih Book, based on the study of the verses and hadiths contained in it as a narrative explanatory study. The method used in this study is a deductive analytical study, whereby the researcher has collected evidence and information related to the subject from the books of interpretations, and the explanations of Sahih Al-Bukhari and others. The most important finding of this study are: Imam al-Bukhari was one of those who has avoided to narrate from the Israelites in the interpretation, except in the very rare; He has arranged the book of interpretation on the surahs of the Qur’an with a brief of each surah; he has taken care of the sciences of the Qur’an in his interpretation; he also has made the basis of his work in the explanation of language by investigating the meanings of words that need clarification. This study also recommends the researchers to pay attention to the classification of the topics of the book of interpretation in Sahih al-Bukhari; And by studying the explanation of the stranger mentioned by Imam Al-Bukhari in the book of interpretation and others.